2017
DOI: 10.1371/journal.pone.0173971
|View full text |Cite
|
Sign up to set email alerts
|

Detection of crossed cerebellar diaschisis in hyperacute ischemic stroke using arterial spin-labeled MR imaging

Abstract: Background and purposeArterial spin-labeling (ASL) was recently introduced as a noninvasive method to evaluate cerebral hemodynamics. The purposes of this study were to assess the ability of ASL imaging to detect crossed cerebellar diaschisis (CCD) in patients with their first unilateral supratentorial hyperacute stroke and to identify imaging or clinical factors significantly associated with CCD.Materials and methodsWe reviewed 204 consecutive patients who underwent MRI less than 8 hours after the onset of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Previous studies have suggested that the remote deactivation of cerebellar neurons can be promoted as a result of the interruption of excitatory impulses by the corticopontocerebellar tract [4]. CCD has been reported in several diseases affecting the brain such as cerebral gliomas [5], epilepsy [6], intracerebral hemorrhage [7, 8], and stroke [3, 911], among others. In the latter, CCD has been detected at the acute, subacute, and chronic phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that the remote deactivation of cerebellar neurons can be promoted as a result of the interruption of excitatory impulses by the corticopontocerebellar tract [4]. CCD has been reported in several diseases affecting the brain such as cerebral gliomas [5], epilepsy [6], intracerebral hemorrhage [7, 8], and stroke [3, 911], among others. In the latter, CCD has been detected at the acute, subacute, and chronic phases.…”
Section: Introductionmentioning
confidence: 99%
“…CCD in human supratentorial brain infarction has been detected with positron emission tomography (PET) and single photon emission computed tomography (SPECT) [13, 14, 1619]. Alternatively to nuclear imaging techniques, arterial spin-labeling (ASL) has also proven efficient for the evaluation of CCD after hyperacute and acute ischemic stroke [9, 20]. Unexpectedly, although CCD has been detected in patients with stroke, the in vivo imaging evaluation of this phenomenon in rodent models of cerebral ischemia has been never evaluated so far.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The subsequent reduction in both blood flow and oxygen extraction fraction in the affected cerebellar hemisphere is traditionally detected with ( 15 O)-H 2 O-PET. 2,[4][5][6][7][8][9] Contemporary MRI techniques, such as dynamic susceptibility contrast MRI [10][11][12] and arterial spin labeling, 13,14 however, may be favored because of better clinical accessibility and absence of exogenous radioisotopes.…”
mentioning
confidence: 99%
“…Diaschisis is explained as a functional depression of cerebello-thalamic-cerebral pathway (Boni et al 1992). Arterial spin labeling imaging can also detect the diaschisis in 75% of patients with hyperacute infarction in the anterior circulation (Kang et al 2017). The occurrence is influenced by the degree of the anterior perfusion reduction and location rather than infarct volume (Sommer et al 2016).…”
Section: Cognitive Functionsmentioning
confidence: 99%